Le Photomontage : un atlas mis en œuvre. Trois ateliers d’arts plastiques en recherche-création dédiés à la composition d’un atlas pour l’avenir du patrimoine industriel - Chimène Denneulin (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Industrial heritage is a fertile ground for creating speculative images. Between nostalgia, criticism and foresight, it brings to light a part of our recent architectural history that clashes with contemporary societal reflections, for which architectural schools in France (ENSA) are a particularly resonant sounding board. The article examines visual material that is useful in experimental situations, through art workshops in architecture schools specifically dedicated to the practice of photomontage. From the problematic archetypes of the industrial imaginary to the manipulative operations that enable forward-looking visions and critical analyses, the photomontage process reveals its relationship with the image atlas and the practical and visual issues that underline its pedagogical and political significance.